THU0382 Venetoclax (ABT-199), A Potent and Selective BCL-2 Inhibitor, Prevents Nephritis in Lupus Prone NZB/W F1 Mice by Depleting Selective Lymphocyte Populations While Sparing Platelets. (9th June 2015) - Wang, L.C.; Perper, S.; Schwartz, A.; Goess, C.; O'Connor, L.; Hartman, D.; Graff, C.; Souers, A.; Leverson, J.; Elmore, S.; Olson, L.
Abstract : Background: Proteins in the BCL-2 family are key regulators of apoptosis, or programmed cell death. Navitoclax, a selective inhibitor of both BCL-2 and BCL-X(L) demonstrated efficacy in the IFN-α induced lupus model in NZB/WF1 mice suggesting that dysregulation of this pathway is operative in lupus disease. However, thrombocytopenia caused by BCL-X(L) inhibition limits the chronic use of this therapeutic agent. We have conducted studies to evaluate a highly potent and orally available BCL-2-selective inhibitor, Venetoclax (ABT-199), for efficacy and mechanism of action in lupus prone NZB/WF1 mouse model. Objectives: To determine the efficacy of Venetoclax and the effect on immune cell subsets in lupus prone NZB/WF1 mice. Methods: NZB/WF1 mice were treated daily for 24 weeks with vehicle or Venetoclax. Proteinuria and survival data are presented as Kaplan-Meyer survival curves. Changes in blood lymphocytes and platelets were assessed by Celldyn blood analyzer. IgG deposition and changes in leukocyte subsets in the kidney were evaluated by immunohistochemistry. Circulating anti-dsDNA antibody levels were determined using a semi-quantitative ELISA assay. In a separate study NZB/WF1 mice were treated daily with vehicle or Venetoclax at 30mg/kg for 16 weeks, leukocyte subsets in spleen, kidney and bone marrow were analyzed by flow cytometry Results: Venetoclax dose-dependently reduced the incidence of severe proteinuria compared to vehicle control and conferred 100% survival at the higher doses in NZB/W F1 lupus mice. Venetoclax attenuated glomerulonephritis, tubular dilatation and IgG deposition in the kidney as well as reductions in numbers of B220+, CD3+, F4/80+ and CD138+ cells compared with vehicle-treated mice. Consistent with its BCL-2 selectivity profile, Venetoclax efficacy in NZB/WF1 mice correlated with a dose-dependent reduction of lymphocytes in peripheral blood (45% reduction for ABT-199 11mg/kg vs. vehicle; 70% reduction for ABT-199 100 mg/kg vs. vehicle) with no effect on platelet numbers. Venetoclax also demonstrated a significant reduction in the numbers of splenic T cells (CD4+, CD8+), B cells (transitional 2, germinal center, and mature). Interestingly, other B cell subsets (transitional 1, marginal zone, and B1) were largely unaltered. Venetoclax did not impair early B cell development or the number of CD138+ long-lived plasma cells in the bone marrow. These data were consistent with the unaltered anti-dsDNA titers in these animals. Conclusions: Treatment of lupus prone NZBW/F1 mice with Venetoclax resulted in preservation of renal function and complete protection against severe proteinuria and mortality. Venetoclax treatment resulted in lymphopenia and a reduction of cell infiltration into the kidney while sparing circulating platelets. Splenic marginal zone B cells, the first line of defense against blood-borne pathogens, were resistant to Venetoclax. Taken together, these data underscore the essential role of BCL-2 in the pathogenesis of lupus and support a role for BCL-2 selective inhibition in the treatment of autoimmunity. Disclosure of Interest: L. C. Wang Shareholder of: Abbvie, S. Perper Shareholder of: Abbvie, A. Schwartz Shareholder of: Abbvie, C. Goess Shareholder of: Abbvie, L. O'Connor Shareholder of: Abbvie, D. Hartman Shareholder of: Abbvie, C. Graff Shareholder of: Abbvie, A. Souers Shareholder of: Abbvie, J. Leverson Shareholder of: Abbvie, S. Elmore Shareholder of: Abbvie, L. Olson Shareholder of: Abbvie